Debt owed to the source code makers. - Parr, Chris (Times Higher Education, 2013)
The article calls upon the higher education sector to acknowledge the important role of research software engineers as computer code makers in research projects. The 2009 Climategate scandal is cited as an example of the potential consequences of research software engineers leaving the industry for the academy. Experts stress the need to ensure the integration of computer code writers as valued members of the research team, and to place greater value on their output.